Determinan Kinerja Pegawai KPU Kabupaten Bogor: Peran Lingkungan, Stres Kerja, dan Disiplin - Ali Yapi; Yuridistya Primadhita; Anggraita Primatami; Idham Maulana Oktora (Jaanur Elbarik Indonesia, 2026)
This study examines the effect of work environment, job stress, and work discipline on employee performance at the General Election Commission (KPU) of Bogor Regency. The objective is to analyze both the partial and simultaneous influence of these three variables on performance. The research uses a quantitative approach with a survey method. Data were collected from employees of KPU Bogor Regency using structured questionnaires and analyzed using multiple linear regression. The results show that the work environment, job stress, and work discipline simultaneously have a significant effect on employee performance. The significance values for the work environment, job stress, and work discipline indicating that each variable individually contributes to improving or decreasing employee performance. These findings demonstrate that a supportive work environment, well-managed job stress, and strong discipline are crucial determinants of employee performance at KPU Bogor Regency. The study concludes that improving organizational conditions related to these factors will enhance employee performance and support the effectiveness of public service institutions